Cobalt-Induced Cytotoxicity in E. coli (DH5α) is Mediated by Modulation of Cellular Phospholipid Composition (Journal of Advanced Microbiology, 2024)
The mechanism of Co2+-induced cytotoxicity in bacteria was evaluated using E. coli (DH5α) as a model system. In E. coli (DH5α), Co2+-induced cytotoxicity was characterized by a dose-dependent (i) reduction of growth rate, (ii) decrease in catalase activity and (iii) decrease in cytosolic free iron content, showing that Co2+-induced cytotoxicity enhances oxidative stress in E. coli. Co2+ induced lipotoxicity in E. coli (DH5α) as indicated by a dose-dependent enhancement of total cellular phospholipid content and increased lipid peroxidation. Lipid peroxidation was mediated through formation of conjugated diene and lipid hydoperoxides folds. A quantitative analysis of total phospholipids using 2D-TLC showed that Co2+-induced toxicity led to modulation of cellular phospholipid (PL) content in E. coli (DH5α). Sum total of phosphatidyl ethanolamine (PE) and phosphatidyl glycerol (PG) (PE+PG) content was increased by 15 % that was accompanied by ~2 fold increase in cardiolipin (CL) content. As CL is known to be augmented in multiple growth inhibitory conditions, we hypothesize that enhanced CL content is a regulatory mechanism of E. coli to survive Co2+-induced cytotoxicity.